Burnout syndrome prevalence in academic nursing student at the University of Costa Rica - Bolaños Reyes, Natalia (2016)
Introduction. The burnout syndrome is usually more researched in the workplace, but those working are not the only individuals who suffer from this syndrome, also many students are immersed in this situation, due to both academic load and personnel required to meet all university requirements.Method. The population is made by the students of the Bachelor of Nursing, School of Nursing at the University of Costa Rica. The design methodology is quantitative, not experimental, with transeccional descriptive scope.Results. 18.8% of the study population presents academic Burnout syndromeConclusion. Most of the population has physical symptoms such as headaches, sleep disorders and musculoskeletal problems. In addition to behavioral symptoms such as irritability, nervousness, feelings of emptiness and loneliness, and cognitive symptoms such as difficulty concentrating and increased sensitivity to criticism that eventually may be open to other ailments both physical and psychiatric way